Predictors of access to healthcare professionals for people with intellectual disability in Ireland. (March 2022) - Doyle, Anne; O'Sullivan, Michael; Craig, Sarah; McConkey, Roy
The Irish National Intellectual Disability Database is updated annually and in 2017 contained records for nearly 22, 000 persons aged 15 years and over. Information was extracted on the contacts each person had with one of eight health professionals in the years 2007, 2012 and 2017. Over these years, there was an increase in the number of people in contact with any professional or with four and more professionals. Nevertheless, the people less likely to have contact were those with milder forms of intellectual disability, persons living with family carers or independently and those linked to smaller provider agencies. By contrast, the odds of people with more severe disability in residential settings were up to eight times greater for having contact with four or more different professionals. As demand for healthcare grows due to increased longevity and service models shift to the community, redeployment of existing professional resources will be needed along with a review of the skill mix.